Unrecognized coronary vasospasm in patients referred for percutaneous coronary intervention: Intracoronary nitroglycerin, the forgotten stepchild of cardiovascular guidelines. Issue 7 (20th March 2017) - Vishnevsky, Alec; Julien, Howard M.; Fischman, David L.; Walinsky, Paul; David Ogilby, J.; Ruggiero, Nicholas J.; Jasti, Babu; Savage, Michael P.
Abstract : Objective: The goal of this study was to demonstrate the importance of intracoronary nitroglycerin (IC NTG) administration during diagnostic coronary angiography and prior to percutaneous coronary intervention (PCI). Background: PCI has been a mainstay treatment for patients with symptomatic coronary artery disease. While current guidelines emphasize the importance of periprocedural antithrombotic medications, they fail to mention the use of nitroglycerin prior to PCI. Methods: Retrospective chart and angiographic review was performed to identify patients referred for PCI who had significant angiographic stenoses that resolved after administration of IC NTG. Results: The study group consisted of 6 patients (3 men, 3 women) with mean age 52 ± 4years (range 46–57 years). All had anginal symptoms and significant (>70%) stenosis on diagnostic coronary angiography. None had documented ST segment elevation. The median interval between diagnostic and staged PCI procedures was 3 days. IC NTG was not administered to any of the patients at the time of diagnostic coronary angiography. In each case, repeat coronary angiography following administration of IC NTG (155 ± 46 mcg) before planned PCI demonstrated resolution of the target stenosis. PCI was deferred and all patients were successfully managed medically. Conclusion: Coronary artery spasm is an under‐recognized cause of chest pain in patients with significant angiographic lesions. Coronary spasm should be suspected especially in younger patients (less than 60 years old) with apparent single vessel disease. IC NTG should be routinely administered during diagnostic angiography and before PCI to avert unnecessary coronary interventions. © 2017 Wiley Periodicals, Inc.